The Homonymy of Sikka Vernacular Language with Sikka Krowe Dialect - Martha Dua Sary, Maria Petrasia; Zulaeha, Ida; Mardikantoro, Hari Bakti (Universitas Negeri Semarang, 2021)
Sikka vernacular language is an isolative language that has various phenomena. One of them is the homonym phenomenon, in which a word has multiple meanings. This research explains the homonym types and the cultural meaning of the homonym in the Sikka vernacular language with the Sikka Krowe dialect. The applied approach was ethnolinguistics to review the language speeches related to cultures. The applied method was qualitative to describe the data in the form of documented data from the source. The applied method was the interview method with the basic technique of recording. The data analysis consisted of a coding method with specific data reduction phases. The results showed that the vernacular language, Sikka, and the dialect, Sikka Krowe had homonym indications in words. They were grouped into homonyms that were homographs and homonyms that were homographs and homophones. Homonyms in Sikka vernacular language and the Sikka Krowe dialect also had meanings, such as Awu, Utan, Daha, and Wua.